The Reliability and Accuracy of Magnetic Resonance Imaging for the Diagnosis of Malignant Breast Lesions - Ahmed, Syed Naseer (Indus Journal of Bioscience Research, 2025)
Objective: Examining the reliability of magnetic resonance spectroscopy in diagnosing malignant breast lesions, with histology serving as the gold standard, is the objective of this study. Methods: In this cross-sectional research 110 females were included. Before collecting data, patients signed a consent form acknowledging the risks. Dynamically enhanced magnetic resonance (MRS) images were studied for their kinematics and morphology. MRS’s choline peak (Cho) was used to detect cancer. Single-voxel technique was used to evaluate MRS’ diagnostic accuracy in cancer. MRS and biopsies were compared. Results: The patients mean age was 48.13±12.54 years and had mean BMI 26.25±9.61 kg/m2. Histological analysis revealed malignant lesions in 82 cases (74.5%), whereas magnetic resonance imaging (MRI) confirmed the presence of malignant lesions in 90 patients (81.8%). When using MRS to diagnose malignant tumors, the most common morphologies observed were ductal enhancement and peripheral enhancement. In terms of specificity, accuracy, sensitivity, NPV, and PPV, MRS demonstrated a performance of 88%, 92%, 72%, and 94%, respectively. Conclusion: The superior specificity, sensitivity, and accuracy of MRS make it an indispensable tool for identifying breast masses. When it comes to diagnosing breast cancer, MRS is a specialized, sensitive, and efficient method.